1990
DOI: 10.1021/bi00469a028
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nuclear matrix DNA topoisomerase II in human leukemia cells resistant to VM-26 and m-AMSA

Abstract: CEM leukemia cells selected for resistance to VM-26 (CEM/VM-1) are cross-resistant to various other DNA topoisomerase II inhibitors but not to Vinca alkaloids. Since DNA topoisomerase II is a major protein of the nuclear matrix, we asked if alterations in nuclear matrix topoisomerase II might be important in this form of multidrug resistance. Pretreatment of drug-sensitive CEM cells for 2 h with either 5 microM VM-26 or 3 microM m-AMSA reduced the specific activity of newly replicated DNA on the nuclear matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 29 publications
1
31
1
1
Order By: Relevance
“…In agreement with our data, a positive correlation was found between mdrl and glutathione-S-transferase mRNA levels in CLL but not the acute leukaemias by Holmes et al (1990b) (Liu, 1989), and similar topoisomerase II activities were found by Holden et al (1990) (Fernandes et al, 1990;DeJong et al, 1990), or the emergence of an altered topoisomerase II enzyme (Pommier et al, 1986) (Madden & Champoux, 1992). Thus, if clinically applicable topoisomerase I specific drugs will be available, their application in those cases eventually could improve chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our data, a positive correlation was found between mdrl and glutathione-S-transferase mRNA levels in CLL but not the acute leukaemias by Holmes et al (1990b) (Liu, 1989), and similar topoisomerase II activities were found by Holden et al (1990) (Fernandes et al, 1990;DeJong et al, 1990), or the emergence of an altered topoisomerase II enzyme (Pommier et al, 1986) (Madden & Champoux, 1992). Thus, if clinically applicable topoisomerase I specific drugs will be available, their application in those cases eventually could improve chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…'Classical' multiple drug resistance (MDR) of cell lines selected in vitro is basically mediated by the P-glycoprotein (for review see Endicott & Ling, 1989). The so-called 'atypical' MDR (at-MDR) where the numerous topoisomerase II inhibitors are affected could be associated with a quantitatively or qualitatively altered activity of topoisomerase II (Pommier et al, 1986;Fernandes et al, 1990;DeJong et al, 1990). Other investigations, however, point to further as yet unrecognised mechanisms or a multifactorial emergence of MDR of in vitro selected cell lines (McGrath & Center, 1988;Deffie et al, 1988;Harker et al, 1989).…”
mentioning
confidence: 99%
“…The total topo II activity in nuclear extracts could be separated in a free and a DNA-bound portion. 21,22 In order to be active and process DNA, the enzyme must bind to the DNA. 20,23,24 As shown in Table 5, the total topo II activity of KG-1 cells is about 50% of the activity of HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The resistance of several leukemia cell lines to anthracyclines and epipodophyllotoxins has been associated with a decreased protein expression and/or activity of topoisomerase II enzymes. [20][21][22][23][24][25] In addition, in some particular cell lines, topoisomerase II gene mutations have been identified and suggested to be responsible for the reduced drug sensitivity to DNA topoisomerase inhibitors. [26][27][28][29] Conversely, more recent studies have shown that increasing the intracellular level of the enzyme by transfection of topoisomerase genes can restore the sensitivity of resistant cancer cell lines to DNA topoisomerase inhibitors.…”
Section: Introductionmentioning
confidence: 99%